The Implications of Fictional Media for Political Beliefs. (January 2013) - Mulligan, Kenneth; Habel, Philip
Most research on media effects in political science deals with the news media or political campaigns. Although some recent work looks at the effects of soft news on beliefs and opinions, little attention has been paid to the potential consequences of media that are fictional. Although viewers typically watch fiction for entertainment, the themes, plots, and dialogue may nevertheless influence their thoughts about politics. This article examines the effects of fiction on political beliefs. We do this in the context of an experimental design, where subjects in the treatment group watched the outlandish movie, Wag the Dog . The results show that those who watched the film were more likely to believe in a far-fetched conspiracy, namely that the U.S. government has and will fabricate a war for political gain. The findings stretch the boundaries of fictional influence by focusing on extreme, conspiratorial beliefs. We suggest that political science and communications scholars should focus greater attention on the implications of fiction for beliefs and attitudes, as the consequences can be perverse.